2015
DOI: 10.1089/jwh.2015.5191
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Unintended Pregnancy: The Contraceptive CHOICE Project in Review

Abstract: The Contraceptive CHOICE Project (CHOICE) sought to reduce unintended pregnancies in the St. Louis Region by removing cost, education, and access barriers to highly effective contraception. CHOICE was a prospective cohort study of over 9,000 women 14-45 years of age who received tiered contraceptive counseling to increase awareness of all reversible methods available, particularly long-acting reversible contraceptive (LARC) methods. Participants were provided with contraception of their choice at no cost for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
151
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(169 citation statements)
references
References 22 publications
7
151
1
10
Order By: Relevance
“…5,6 Although the overall continuation rates of implants are very good compared with short-acting methods, continuation beyond 1 year of use appears lower for implants than other long-acting methods, often secondary to unacceptable bleeding. 3,16 Interventions such as the one tested in this study may be of benefit to women seeking temporary cessation of bleeding episodes and possibly avoid early removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Although the overall continuation rates of implants are very good compared with short-acting methods, continuation beyond 1 year of use appears lower for implants than other long-acting methods, often secondary to unacceptable bleeding. 3,16 Interventions such as the one tested in this study may be of benefit to women seeking temporary cessation of bleeding episodes and possibly avoid early removal.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most effective forms of contraception available with a failure rate of 0.05% 1,2 and 2-year continuation rates are high ranging from 53% to 90%. 3,4 Like other contraceptive methods, many implant users discontinue before the 3 years of intended use for reasons other than desiring pregnancy. One of the most common reasons for lower contraceptive satisfaction is "bleeding problems" such as prolonged bleeding and frequent episodes, which may be termed "bothersome bleeding."…”
mentioning
confidence: 99%
“…While these products are considerably less hazardous to a woman's health than pregnancy, they do increase the risks of venous and arterial thromboembolism [84]. Progestin-only methods, which provide even better pregnancy protection without any pro-thrombotic impacts, have increased in use.…”
Section: Expert Opinionmentioning
confidence: 99%
“…A previous study that was part of the US-based contraceptive CHOICE project reported a reduction in abortion rates with the use of LARC methods among participants who were recruited mainly from two abortion facilities in St Louis, MI, USA. At the end of that study, abortion rates in this group were less than half the regional and national rates 13. According to the results of the present study, an estimated total of 410 unsafe abortions were averted over the 9 years of evaluation.…”
Section: Discussionmentioning
confidence: 51%